Oleaginous yeasts from Antarctica: Screening and preliminary approach on lipid accumulation - Viñarta, Silvana Carolina; Angelicola, María Virginia; Barros, J. Maximiliamo; Fernandez, Pablo Marcelo; Mac Cormack, Walter Patricio; Aybar, Manuel Javier; Castellanos, Lucia Ines (Journal of Basic Microbiology)
The capability of 17 Rhodotorula spp. isolated from Antarctica to accumulate intracellular lipids in nitrogen-limited medium was investigated. As results, 10 isolates were selected by Nile red staining, while 12 isolates were selected as oleaginous by analysis of total lipid content (20.4–73%, w/w of dry biomass). The higher lipid production and accumulation was exhibited for six strains belonging to three species of Rhodotorula (Rhodotorula glutinis, Rhodotorula glacialis, and Rhodotorula laryngis). This is the first report where R. laryngis have been identified within oleaginous specie. Lipid accumulation was evaluated comparatively in two nitrogen-limited glucose-based media (MI and MII). MI (low C/N ratio) was more suitable for biomass and lipid production while in MII (high C/N ratio) total lipid content was improved. R. glutinis R4, R. glacialis R15, and R. glutinis R48 showed high lipid concentrations (4.65–6.93 g L−1) and they were able to accumulate large amounts of lipids per gram of biomass (47–77%, w/w). A similar profile in fatty acids composition and content of neutral lipids to vegetable oils was observed, indicating that lipids produced by oleaginous Antarctic yeasts can be considered an alternative feedstock for biodiesel production. Antarctica represents an important source of oleaginous yeasts with adaptive capabilities to accumulate considerable amounts of lipids with biotechnological interest at 15 °C and 25 °C. Fil: Viñarta, Silvana Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucuman. Planta Piloto de Procesos Industriales Microbiologicos; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Instituto Superior de Investigaciones Biológicas. Universidad Nacional de Tucumán. Instituto Superior de Investigaciones Biológicas; Argentina Fil: Angelicola, María Virginia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico ...